2021
DOI: 10.1016/j.culher.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the xerophilic potential of moulds on selected egg tempera paints on glass and wooden supports using fluorescent microscopy

Abstract: Highlights• 11 fungal isolates from cultural heritage institutions' interiors were screened for xerophilic trait • Specially designed incubators were constructed to hold specific RH levels of 55 %, 63 % and 74 %• Fungal growth was monitored at low relative humidity on wood and glass supports painted by traditional artists' paints • Effects of pigments, support materials and strain variability are discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 83 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the environmental conditions, such as the rate of relative humidity (70-75%) and the low temperature (16-18 • C) established in the Museodivino may have determined and promoted the development of biodeterioration fungal strain. Kosel and co-workers [46] established that relative humidity was the key factor limiting the growth of different fungal biodeteriorating strains on wooden support, in which the fungal growth positively correlated to the relative humidity increasing (from 55 to 74%). Piñar et al [47] reported that temperatures between 18 and 20 • C and humidity of 50-60% are recommended for the effective preservation of documents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the environmental conditions, such as the rate of relative humidity (70-75%) and the low temperature (16-18 • C) established in the Museodivino may have determined and promoted the development of biodeterioration fungal strain. Kosel and co-workers [46] established that relative humidity was the key factor limiting the growth of different fungal biodeteriorating strains on wooden support, in which the fungal growth positively correlated to the relative humidity increasing (from 55 to 74%). Piñar et al [47] reported that temperatures between 18 and 20 • C and humidity of 50-60% are recommended for the effective preservation of documents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if left unchecked, global warming may ultimately impair the habitability of Earth's surface [93]. The ecology of E. halophilicum is complex in as much as-like other fungal xerophiles-this species is commonly found on dry surfaces in nature and surfaces of artifacts and dust particles [50,65,[94][95][96]. Global climate change is causing various perturbations at the regional scale, at some places/times causing drought and at others causing floods.…”
Section: Discussionmentioning
confidence: 99%
“…Both gelatin and paper serve as the primary energy source sustaining biofilm metabolisms; biofilms actively dissolve gelatin and induce chemical alterations in the silver particles within the emulsion, thus causing gradual photograph dissolution. Both bacterial and fungal communities are responsible for attacking photographs, with the former being particularly destructive [9,10]. Recent research has highlighted the compartmentalization of different species within biofilms, each occupying separate niches [11].…”
Section: Biodeterioration Of Modern Artworkmentioning
confidence: 99%